Integrity of the uncinate fasciculus is associated with the onset of bipolar disorder: a 6-year followed-up study - Li, Xiaoyue (Transl Psychiatry, 2021)
Patients with Bipolar Disorder (BD) are associated with aberrant uncinate fasciculus (UF) that connects amygdala-ventral prefrontal cortex (vPFC) system, but the casual relationship is still uncertain. The research aimed to investigate the integrity of UF among offspring of patients with BD and investigate its potential causal association with subsequent declaration of BD. The fractional anisotropy (FA) and mean diffusivity (MD) of UF were compared in asymptomatic offspring (AO, n = 46) and symptomatic offspring (SO, n = 45) with a parent with BD, and age-matched healthy controls (HCs, n = 35). Logistic regressions were performed to assess the predictive effect of UF integrity on the onset of BD. The three groups did not differ at baseline in terms of FA and MD of the UF. Nine out of 45 SO developed BD over a follow-up period of 6 years, and the right UF FA predicted the onset of BD (p = 0.038, OR = 0.212, 95% CI = 0.049–0.917). The ROC curve revealed that the right UF FA predicted BD onset (area-under-curve = 0.859) with sensitivity of 88.9% and specificity of 77.3%. The complementary whole-brain tract-based spatial statistics (TBSS) showed that widespread increases of FA were found in the SO group compared with HCs, but were not associated with the onset of BD. Our data provide evidence supporting the causal relationship between the white matter structural integrity of the amygdala-vPFC system and the onset of BD in genetically at-risk offspring of BD patients.